2023
DOI: 10.1002/srin.202200838
|View full text |Cite
|
Sign up to set email alerts
|

Inclusions in Calcium‐Treated and Resulfurized Al‐Killed Steels

Abstract: The resulfurized steel is widely used in automobiles, machine tools, and other fields due to its high strength, low energy consumption, and good machinability. The high sulfur content in the steel inevitably leads to the precipitation of a large amount of sulfide inclusions with complex morphology and uneven distribution in the steel during the cooling and solidification process. The size, distribution, and morphology of inclusions, especially the manganese sulfide (MnS) in the resulfurized steel, have a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Ju, Lee, and Jang [60] demonstrated the effect of crystallographic texture on the fracture toughness of the API 5L X65 pipeline steel using texture analysis through pole figure measurement of the volume fraction of crystallographic planes as a function of the angle to the rolling direction of the plates. Their results showed that all the planes had uniform distribution, but the {110} plane showed more density in the transverse to the rolling direction [61,62]. The {110} plane is one of the most densely packed planes of body-centered cubic (BCC) ferrite crystals, being, therefore, responsible for the plastic deformation that precedes ductile tearing at the upper shelf regime, and this was the reason the authors provided to explain the higher fracture toughness observed at the transverse direction in comparison to the rolling direction.…”
Section: Tensile and Fracture Toughness Anisotropymentioning
confidence: 99%
“…Ju, Lee, and Jang [60] demonstrated the effect of crystallographic texture on the fracture toughness of the API 5L X65 pipeline steel using texture analysis through pole figure measurement of the volume fraction of crystallographic planes as a function of the angle to the rolling direction of the plates. Their results showed that all the planes had uniform distribution, but the {110} plane showed more density in the transverse to the rolling direction [61,62]. The {110} plane is one of the most densely packed planes of body-centered cubic (BCC) ferrite crystals, being, therefore, responsible for the plastic deformation that precedes ductile tearing at the upper shelf regime, and this was the reason the authors provided to explain the higher fracture toughness observed at the transverse direction in comparison to the rolling direction.…”
Section: Tensile and Fracture Toughness Anisotropymentioning
confidence: 99%